The process of lithography - Memorial University of Newfoundland. Educational Television Centre (Memorial University of Newfoundland. Extension Service, 1980)
Filmed at St. Michael's Printshop in Newfoundland, visual artist Don Wright explains and demonstrates how lithographic prints are made